Education and the moderating roles of age, sex, ethnicity and apolipoprotein epsilon 4 on the risk of cognitive impairment - Makkar, Steve R. (Arch Gerontol Geriatr, 2020)
BACKGROUND: We examined how the relationship between education and latelife cognitive impairment (defined as a Mini Mental State Examination score below 24) is influenced by age, sex, ethnicity, and Apolipoprotein E epsilon 4 (APOE*4). METHODS: Participants were 30,785 dementia-free individuals aged 55–103 years, from 18 longitudinal cohort studies, with an average follow-up ranging between 2 and 10 years. Pooled hazard ratios were obtained from multilevel parametric survival analyses predicting cognitive impairment (CI) from education and its interactions with baseline age, sex, APOE*4 and ethnicity. In separate models, education was treated as continuous (years) and categorical, with participants assigned to one of four education completion levels: Incomplete Elementary; Elementary; Middle; and High School. RESULTS: Compared to Elementary, Middle (HR = 0.645, P = 0.004) and High School (HR = 0.472, P < 0.001) education were related to reduced CI risk. The decreased risk of CI associated with Middle education weakened with older baseline age (HR = 1.029, P = 0.056) and was stronger in women than men (HR = 1.309, P = 0.001). The association between High School and lowered CI risk, however, was not moderated by sex or baseline age, but was stronger in Asians than Whites (HR = 1.047, P = 0.044), and significant among Asian (HR = 0.34, P < 0.001) and Black (HR = 0.382, P = 0.016), but not White, APOE*4 carriers. CONCLUSION: High School completion may reduce risk of CI associated with advancing age and APOE*4. The observed ethnoregional differences in this effect are potentially due to variations in social, economic, and political outcomes associated with educational attainment, in combination with neurobiological and genetic differences, and warrant further study.